Implementación de un módulo automatizado para el proceso académico y administrativo de titulación en la carrera de Computación de la Universidad Nacional de Loja - Sarmiento Cuenca, Luis Alberto (2024)
To answer the research question of the present TIC, two objectives were set, To implement the deployment of the degree process automation through Bonitasoft; and To statistically determine the perceived usefulness of the control and monitoring of the degree works through the case study Computation, whose results have the purpose of improve the current process and reduce the execution time of the phases of the current process in current RRA of the UNL, in this way the module corrects and provides a solution to the problem posed. Therefore, to comply with the general objective planned in this TIC, the current process was surveyed, proposing the process automation, and including the legalization of documents through electronic signature, with the help of the agile XP methodology, information gathered from the literature review, application of surveys and interviews; The automated module was then developed employing tools such as Bonitasoft Community, which provides capabilities business process management and development, as well as BPMN process design, Alfresco, for document storage, and SMTP of Google for emails, resulting in the automated TIC process module, which was presented to the stakeholders involved in the degree process. Finally, functional and acceptance tests were performed to obtain the results of the improvement of the current process with the comparison of the new process at implementing this module. To determine the perceived usefulness statistically, TAM was applied, using an instrument (survey) of ten items, of which six were based on the Likert scale and four were dichotomous, to obtain the degree of reliability of this instrument Cronbach's Alpha was implemented and finally to conclude with the statistical data, the Normal Distribution of Perceived Usefulness and Perceived Ease of Use were used. Keywords: BPMN, TIC, automation, Bonitasoft, XP methodology, eSignature